UJI AKTIVITAS ANTIBAKTERI EKSTRAK SPONS Callyspongia aerizusa DARI PERAIRAN DESA POOPOH KABUPATEN MINAHASA - Viocindy Riska Nusaly; Defny S.Wewengkang; Erladys Rumondor (UNIVERSITAS SAM RATULANGI, 2024)
Callyspongia aerizusa is one of the sponge species that is spread across the Indonesian marine waters and rich in bioactive compounds such as secondary metabolites that is used in medicine field as antibacterial but still not widely used by the people. The improvement of bacteria resistant has been a serious problem in the medicine field, therefore there should be an improvement of a new antibiotic medicine from natural ingredients for the healt improvement. This research aims to find the activity of extracts of sponge Callyspongia aerizusa from the waters of Poopoh Village, Minahasa Regency against the growth of Pseudomonas aeruginosa and Staphylococcus aureus bacteria. The growth of bacterial is tested by disc diffusion Kirby Bauer method and by observing the value of generated inhibition zone. From the result of the research, the extracts of Callyspongia aerizusa sponge has clear zone against Staphylococcus aureus bacteria of 8 mm in the concentration of 250 µg/disc, and the Pseudomonas aeruginosa bacteria has 9 mm in the concentration of 250 µg/disc which categorized as medium. It can be concluded that the Callyspongia aerizusa sponge has an metabolite compound with wide spectrum activity that can hinder the growth of Gram-negative and Gram-positive bacteria